2008
DOI: 10.1117/1.3006072
|View full text |Cite
|
Sign up to set email alerts
|

Application of attenuated total reflection Fourier transform infrared imaging and tape-stripping to investigate the three-dimensional distribution of exogenous chemicals and the molecular organization in Stratum corneum

Abstract: Attenuated total reflection Fourier transform infrared spectroscopic imaging combined with tape-stripping is an advantageous approach to map the depth penetration and lateral distribution of topically applied chemicals in Stratum corneum (SC) and the conformational order of SC lipids. Tape-stripping progressively removes layers of SC, and chemical imaging provides spatially resolved information on the chemical composition of both the newly exposed SC surface and of the tapes used for stripping. The procedure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…whether it was exogenous, because of surface contamination, or endogenous, where arsenic is embedded in the protein matrix during the nail growth. The extensive information on biomedical applications of these methods for structural and chemical tissue diagnostics can be found in the review by Krafft and Sergo [90] and in several recent papers related to modifications of these methods for high-resolution chemical imaging of biological cells and tissues, see for example the paper by Boncheva et al [91] Conclusions In this study we tested a combination of synchrotron microprobe XRF and XAS methods and the bulk XAS method to study arsenic speciation in nail clippings of volunteers exposed to slightly elevated levels of As in drinking water. It is encouraging that the XAS techniques showed a relatively high sensitivity for the chemical speciation analysis in nail clippings collected from a low level arsenic exposure cohort.…”
Section: Resultsmentioning
confidence: 98%
“…whether it was exogenous, because of surface contamination, or endogenous, where arsenic is embedded in the protein matrix during the nail growth. The extensive information on biomedical applications of these methods for structural and chemical tissue diagnostics can be found in the review by Krafft and Sergo [90] and in several recent papers related to modifications of these methods for high-resolution chemical imaging of biological cells and tissues, see for example the paper by Boncheva et al [91] Conclusions In this study we tested a combination of synchrotron microprobe XRF and XAS methods and the bulk XAS method to study arsenic speciation in nail clippings of volunteers exposed to slightly elevated levels of As in drinking water. It is encouraging that the XAS techniques showed a relatively high sensitivity for the chemical speciation analysis in nail clippings collected from a low level arsenic exposure cohort.…”
Section: Resultsmentioning
confidence: 98%
“…It has also been shown that ATR-FTIR imaging provides information on the swelling of the stratum corneum as a function of humidity. This approach was also used to image the penetration of liquid ethanol into the skin [77] and showed good potential for studying the transdermal delivery of drugs [78,79].…”
Section: Imaging Of Water Sorption In Pharmaceutical Formulations Andmentioning
confidence: 99%
“…11,31 This study demonstrated the possibility of measuring SC heterogeneity by observing lipidrich and lipid-poor regions, and the permeation and distribution of a model drug and solvents into the SC. Although this spectroscopic approach measures permeation through the skin, it is not a straightforward method for the accurate calculation of diffusion coefficients because the ATR crystal is present on one side of the skin instead of in an infinite sink.…”
Section: Introductionmentioning
confidence: 97%
“…To obtain a diffusion coefficient, it is possible to apply a Franz-type cell, as was used by Hartmann et al, 9 in conventional ATR spectroscopic studies or in combination with a tape strip in ATR-FTIR imaging. 31 The ATR-FTIR imaging approach presented here studies permeation of a solvent and model drug through the skin.…”
Section: Introductionmentioning
confidence: 99%